Decarbonylative Issues Involved in Ru(II)‐Catalyzed [6+2−1] Annulation Reaction of Hydroxychromone with Alkyne: A DFT Study. Issue 2 (9th December 2020) - Ling, Baoping; Wang, Jiarong; Liu, Yuxia; Jiang, Yuan‐Ye; Liu, Peng; Feng, Jin; Bi, Siwei
Abstract: Density functional theory calculations have been performed to explore the Ru‐catalyzed decarbonylative annulation reaction of 3‐hydroxy‐2‐phenyl‐chromone with an alkyne to synthesize spiroindenebenzofuranones. A Ru(II)−Ru(0)−Ru(II) rather than a Ru(II)−Ru(IV)−Ru(II) transformation was found involved in the decarbonylation process, which is responsible for the sequence of alkyne insertion/decarbonylation. Oxidative addition of C(carbonyl)−C(carbonyl) bond to Ru(0) and the Ru(II)−C(sp 2 ) bond formation were confirmed to be favorable for the decarbonylation, meanwhile oxidative addition of C(carbonyl)−C(carbonyl) bond to Ru(0) is likely to be the rate‐determining step for the entire catalytic cycle. It is predicted that the regeneration of the catalyst was achieved by the oxidation of air oxygen in the absence of other oxidants. The current theoretical study provides new insights into the decarbonylative annulation. Abstract : DFT calculations have been used to explore the Ru‐catalyzed decarbonylative annulation of 3‐hydroxy‐2‐phenyl‐chromone with alkynes to synthesize spiro‐indenebenzofuranones. A Ru(II)−Ru(0)−Ru(II) transformation was found to be involved in the decarbonylation process. The oxidative addition of C(carbonyl)−C(carbonyl) bond to Ru(0) is likely the rate‐determining step. The regeneration of the catalyst is likely achieved by oxidation with air oxygen.